Does the Rarity of a Flower’s Scent Phenotype in a Deceptive Orchid Explain Its Pollination Success? - Braunschmid, Herbert; Dötterl, Stefan (Frontiers in Plant Science, 2020)
Floral scent, a key mediator in plant–pollinator interactions, varies not only among plant species, but also within species. In deceptive plants it is assumed that floral scents and other traits involved in pollinator attraction are under negative frequency-dependent selection, and here, we tested for the first time, whether this process is acting on floral scent bouquets. If true, we expect that pollinators will visit flowers with rarer scents within a population more frequently than flowers with more common scents. The deceptive orchid Cypripedium calceolus, pollinated mainly by bees, was our study species. We collected the scent of more than hundred flowers in two populations by dynamic headspace and analyzed the samples by gas chromatography coupled to mass spectrometry (GC/MS). From the same plant individuals we also recorded whether or whether not they set fruits. Univariate and multivariate approaches allowed us to obtain rarity measures of floral scent for all single plant individuals. These were calculated on the total quantity of scent and on relative and qualitative properties of the multivariate scent blends. We investigated whether flowers with rarer scents are more likely to produce a fruit than those with more common scent chemotypes. Our results do not show rarity has an effect on the likelihood to set fruits in any of the two populations and in any of the scent characteristics analyzed. Hence, there is no evidence of negative frequency-dependent selection mediated by pollinators and acting on the floral scent of C. calceolus. We discuss that our new approach to determine rarity of a scent is applicable to any univariate or multivariate (semi)quantitative trait.